Catheter-Obtained Urine Culture Contamination Among Young Infants: A Prospective Cohort Study - Bahat, Hilla; Apelman Cipele, Revital; Maymon, Tali; Youngster, Ilan; Goldman, Michael (Frontiers in Pediatrics, 2021)
Objectives A correct diagnosis of urinary tract infection in young infants requires an uncontaminated urine culture, commonly obtained by urethral catheterization. In the current study we examined the rates and factors associated with contaminations of catheter-obtained urine cultures in very young infants. Methods This prospective cohort study included 143 catheter obtained urine cultures of infants≤2 months of age admitted to the pediatric ward of a tertiary hospital in Israel from April 2019 to September 2020. Patient's and operator's study variables were documented at the time of catheter insertion. Positive urine cultures were reviewed by a Pediatric Nephrologist and a Pediatric Infectious disease specialist and designated as infection or contamination. The study variables were compared between those with or without contamination. Results The contamination rate in our cohort was 29%. Females were more than twice as likely to have a contaminated urine culture (37% vs. 18% respectively, P=0.014). Circumcision status, official training about sterile catheterization, a sense of difficult catheterization and the shift in which the culture was obtained didn't influence the contamination rate. Conclusions Catheter-obtained urine cultures have a high contamination rate among very young infants, especially among girls.